Antibiotic usage and stewardship in patients with COVID-19: too much antibiotic in uncharted waters?. Issue 3 (May 2021) - Evans, Terry John; Davidson, Harriet Claire; Low, Jen Mae; Basarab, Marina; Arnold, Amber
Background: Antimicrobial usage and stewardship programmes during COVID-19 have been poorly studied. Prescribing practice varies despite national guidelines, and there is concern that stewardship principles have suffered. Aim: To analyse antibiotic prescriptions during the COVID-19 pandemic at a teaching hospital and to propose improved approaches to stewardship. Methods: We reviewed COVID-19 admissions to medical wards and intensive care units (ICUs) in a London teaching hospital to assess initial antibiotic usage and evidence of bacterial co-infection, and to determine if our current antibiotic guidelines were adhered to. Findings: Data from 130 inpatients (76% medical and 24% ICU) were obtained. On admission, 90% were treated with antibiotics. No microbiological samples taken on admission provided definitive evidence of respiratory co-infection. In 13% of cases, antibiotics were escalated, usually without supporting clinical, radiological or laboratory evidence. In 16% of cases, antibiotics were stopped or de-escalated within 72 h. Blood results and chest radiographs were characteristic of COVID-19 in 20% of ward patients and 42% of ICU patients. Overall mortality was 25% at 14 days – similar to rates described for the UK as a whole. Conclusion: The majority of patients received antibiotics despite limited evidence of co-infection. Most patients received narrower spectrum antibiotics than recommended by NICE. As understanding of the natural history of COVID-19 infections progresses, stewardship programmes will need to evolve; however, at this point, we feel that a more restrictive antibiotic prescribing approach is warranted. We propose strategies for effective stewardship and estimate the effect this may have on antibiotic consumption.